2018
DOI: 10.1155/2018/6238989
|View full text |Cite
|
Sign up to set email alerts
|

Clocking In Time to Gate Memory Processes: The Circadian Clock Is Part of the Ins and Outs of Memory

Abstract: Learning, memory consolidation, and retrieval are processes known to be modulated by the circadian (circa: about; dies: day) system. The circadian regulation of memory performance is evolutionarily conserved, independent of the type and complexity of the learning paradigm tested, and not specific to crepuscular, nocturnal, or diurnal organisms. In mammals, long-term memory (LTM) formation is tightly coupled to de novo gene expression of plasticity-related proteins and posttranslational modifications and relies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 122 publications
1
22
0
Order By: Relevance
“…Using enrichment network analysis after annotating the upregulated DEGs through the KEGG pathway database, we found that the most significant change occurred in the MAPK signaling pathway (also known as the Ras-Raf-MEK-ERK pathway) (Fig 3c). Circadian genes have recently been shown to be involved in hippocampus-dependent memory (56,57), and the lack of functional Per1 in the hippocampus impairs object location memory (58) and LTP (59). As predicted, based upon the downregulation of circadian pathways we observed after learning in CBP KIX/KIX mice, we also found pathways related to circadian rhythm and circadian entrainment to be upregulated following spatial learning in WT mice.…”
Section: Spatial Learning Induces Cbp Downstream Genes In Wt Micesupporting
confidence: 79%
“…Using enrichment network analysis after annotating the upregulated DEGs through the KEGG pathway database, we found that the most significant change occurred in the MAPK signaling pathway (also known as the Ras-Raf-MEK-ERK pathway) (Fig 3c). Circadian genes have recently been shown to be involved in hippocampus-dependent memory (56,57), and the lack of functional Per1 in the hippocampus impairs object location memory (58) and LTP (59). As predicted, based upon the downregulation of circadian pathways we observed after learning in CBP KIX/KIX mice, we also found pathways related to circadian rhythm and circadian entrainment to be upregulated following spatial learning in WT mice.…”
Section: Spatial Learning Induces Cbp Downstream Genes In Wt Micesupporting
confidence: 79%
“…3 c). Circadian genes have recently been shown to be involved in hippocampus-dependent memory [ 56 , 57 ], and the lack of functional Per1 in the hippocampus impairs object location memory [ 58 ] and LTP [ 59 ]. As predicted, based upon the downregulation of circadian pathways we observed after learning in CBP KIX/KIX mice, we also found pathways related to circadian rhythm and circadian entrainment to be upregulated following spatial learning in WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…Here, more than 10% of genes and proteins show circadian fluctuations (Debski et al, 2017) and are associated with changes in synaptic excitability (Barnes et al, 1977). Learning and memory formation, two functions that are conserved across species and that in mammals rely on the activity of the hippocampal formation, are also modulated by circadian rhythms (Gerstner et al, 2009;Rawashdeh et al, 2018;Ruby et al, 2008;Shimizu et al, 2016;Smarr et al, 2014;Snider et al, 2016). For example, mice trained to context fear conditioning protocols acquire the conditioning more slowly if trained during the dark (D) phase of the circadian cycle (ZT12-24) (Chaudhury and Colwell, 2002), a time when long-term plasticity at Schaffer collateral synapses is also reduced Abzug, 1977, 1978).…”
Section: Introductionmentioning
confidence: 99%